9 Are We Ready for Outpatient Acute Heart Failure Management (Frusemide Lounges and Beyond)?-A Nationwide Survey of UK Acute Heart Failure Practice. (3rd June 2016) - Mohee, Kevin; Wong, Kenneth
Abstract : Purpose: Heart failure (HF) has a prevalence of over 750, 000 people in the UK and over 23 million worldwide. In response to the burden of hospital readmissions and post hospitalisation needs of HF patients, recent health policies stress the need to develop services that will cater for patients' requirements and deliver these closer to their home. One such service is out of hospital parenteral diuretic treatment, which is supported by data from observation studies although there may be observation bias. We aimed at carrying out an online survey to evaluate use of outpatient acute HF management in the UK and assessing the feasibility of setting up a randomised control trial (RCT) comparing inpatient versus outpatient acute heart failure management in the UK. Method: We developed a brief online survey by using SurveyMonkey® (Palo Alto, Calif) that was sent to 237 consultant cardiologists with an interest in heart failure in the UK identified from the Directory of Cardiology 2014. The survey was available from 26 February through 10 March 2015 and comprised questions regarding existence of an outpatient acute heart failure service (frusemide lounge) at the hospital where the consultant currently works, whether hospital/PCT currently support a community based acute heart failure management service including the use of parenteral frusemide, identity of person who delivers the community parenteral frusemide service, interest to take part in a multi-centre randomised controlled trial comparing outpatient acute heart failure management with standard inpatient care and if so the number of patients that can potentially be randomised over the next 2 years. Results: The survey was sent by direct e-mail invitation to 237 cardiologists; 55 (23%) took and completed the survey. 14 (25%) indicated existence of an outpatient acute heart failure service (frusemide lounge) at the hospital where they currently work and 14 (25%) mentioned that their hospital/PCT currently support a community based acute heart failure management service including the use of parenteral frusemide. Of these 14 (25%) centres, in 5 (9%) delivery of the community parenteral frusemide service was provided by district nurses, 2 (3.5%) by GP, 7 (12.5%) by heart failure nurse and 1 (1.7%) by an ambulatory care unit. Finally 21 (37.5%) expressed an interest in taking part in a multi-centre randomised controlled trial comparing outpatient acute heart failure management with standard inpatient care. Conclusion: Our study shows that only a very small minority of hospitals in the UK offers an outpatient based acute heart failure management such as frusemide lounges. No RCT has investigated the clinical effectiveness and safety of outpatient IV diuretic therapy in patients with decompensated HF yet. Hence our aim is to carry out the first RCT looking at safety and effectiveness of Out-of-hospital Acute Heart failure Care compared with inpatient management in the UK.